Profitability and Activity Ratio in Measuring Financial Performance - Mulyana Machmud; Bakhtiar Tijjang; Nirvana Latif; Hendra Hermawan; Waty Rusman Salehe (www.amertainstitute.com, 2024)
This study examines the impact of profitability and activity ratios on the financial performance of Regional Drinking Water Companies (PDAM). The research utilizes financial reports as the primary object of analysis. Data collection methods include observation, interviews, documentation, and library research, ensuring a comprehensive understanding of the subject matter. The data analysis approach employed is descriptive analysis, involving data collection, classification, explanation, and analysis to present clear and systematic information regarding the issues under investigation. The findings reveal that the profitability ratio significantly influences PDAM's financial performance, indicating the company's ability to generate profits plays a critical role in determining financial stability and operational success. Similarly, the activity ratio, which measures the efficiency of a company's operations and resource utilization, also shows a significant impact on financial performance. These results highlight the importance of effective management of profitability and activity ratios in enhancing the financial health of PDAM. By maintaining a balance between profitability and operational efficiency, PDAM can achieve sustainable financial performance. This study underscores the need for PDAM to regularly evaluate these financial ratios as part of their strategic decision-making process to ensure continued growth and improved service delivery.